Nonlinear response of nitric oxide emissions to a nitrogen application gradient: A case study during the wheat season in a Chinese rice-wheat rotation system. (February 2015) - Zhao, Miao; Tian, Yuhua; Zhang, Min; Yao, Yuanlin; Ao, Yuqin; Yin, Bin; Zhu, Zhaoliang
Abstract: The response of nitric oxide (NO) emissions to nitrogen (N) input in agricultural ecosystems is generally assumed to be linear, but the availability of inorganic soil N exceeding crop N demands may cause a threshold response of NO. We conducted a four-rotation field measurement with discrepant N fertilizer rates during the wheat season of the rice-wheat rotation in the Taihu Lake region in China to test the hypothesis. Across all years, a nonlinear model well characterized the response of cumulative NO emissions to N fertilizer rates. The direct emission factors of NO induced by fertilizer also increased nonlinearly with increasing N doses, with a mean of 1.06% (ranging from 0.54% to 1.49%). NO emissions were low (<1.81 kg N ha −1 yr −1 ) over the 0–180 kg N ha −1 fertilizer additions; above these additions, the increasing N rates resulted in substantial NO increases ranging from 73% to 245% but only elevated crop yields by 6%. The results suggested defining the N rate of 180 kg N ha −1 as a promising level for achieving decreased NO emissions without greatly affecting the economic return from grain yield. Highlights: Nonlinear response of cumulative NO emissions to N application rates was observed. Direct emission factors of NO increased nonlinearly with increasing N rates. Optimum N use mitigated substantial NO emissions with little yield penalty.